The Effect of Explicit Instruction on Implicit and Explicit Linguistic Knowledge in Kindergartners. Issue 2 (3rd April 2022) - Spit, Sybren; Andringa, Sible; Rispens, Judith; Aboh, Enoch O.
ABSTRACT: Research consistently shows that adults engaged in tutored acquisition benefit from explicit instruction in several linguistic domains. For preschool children, it is often assumed that such explicit instruction does not make a difference. In the present study, we investigated whether explicit instruction affected young learners in acquiring a morpho-syntactic element. A total of 103 Dutch-speaking kindergartners ( M = 5;7) received training in a miniature language to learn a meaningful agreement marker. Results from a picture matching task, during which eye movements were recorded, provided no evidence that explicit instruction led to higher accuracy rates, but suggest that it did lead to earlier predictive eye movements. These data seem incompatible with the idea that explicit instruction does not make a difference when kindergartners learn a grammatical element, and tentatively suggest that explicit instruction has a different effect on explicit knowledge than on implicit knowledge in this age group.